LEI 10.639/03: O QUE OS ALUNOS DO 1°ANO DO ENSINO MÉDIO SABEM SOBRE A HISTÓRIA AFRICANA E AFRO-BRASILEIRA? - Janz, Rubia Caroline (2016)
It seems that there is racial prejudice in the History of mankind since the birth of power relations between men. Nevertheless, since ancient times to the present day,human rights and coping mechanisms have greatly evolved, what might lead us to believe that such a practice is a problem close to being solved. However, we realize that racism presents new facets, more discrete and concealed, but still part of human societies. This is very clear in Brazil, where there is a type of cordial racism, silent and without actors, especially in relation to African descents. After years of claims, the black movement managed to achieve the law 10.639 / 03, which requires teaching of African-Brazilian History and African culture in basic education. The work aims to raise data by means of semi-structured quiz applied to students of Ponta Grossa city, Parana. It was elaborated based on Diretrizes Curriculares Nacionais (National Curriculum Guidelines) according to what the law 10639/13 proposes and it was analyzed both by a quantitative bias like for a qualitative. From the data obtained, it has the intention to answer the following questions: - what do students of the 1st year of high school know about Afro-Brazilian and African History and Culture? What representations do they build about the African continent, its culture and its people? To answer such questions we will use the theory of social representations of Serge Moscovici and the concept of Historical consciousness developed by Jörn Rüsen. The survey results showed that there is a progress in compliance with the law, especially regarding to how the contents are being worked out, but we still need more effort from all sectors involved in the History teaching and learning process so that the new issues required, mainly related to the African History, are in fact, embedded. Moreover, it can be seen that the representations these students build on the African continent are still stereotyped and reductionist, although there is a contrary movement towards recognition of some cultural practices and their influence on the construction of Brazilian culture and identity.